Manufacturing process of a brain aneurysm biomodel in PDMS using rapid prototyping - Souza, Andrews (2019)
Cerebral aneurysm is an abnormal dilatation of the blood vessel into a saccular form. They can originate in congenital defects, weakening of the arterial wall with increasing age, atherosclerotic changes, trauma and infectious emboli. The in vivo experiments are an effective way of investigating the appearance, validating new practices and techniques, but beyond ethical issues, these types of experiments are expensive and have low reproducibility. Thus, to better understand the pathophysiological and geometric aspects of an aneurysm, it is important to fabricate in vitro models capable of improving existing endovascular treatments, developing and validating theoretical and computational models. Another difficulty is in the preoperative period of the non-ruptured cerebral aneurysm, known for the success of the skilled acts because there is an anatomical structure of the aneurysm as its current position. Although there are technologies that facilitate three-dimensional video visualization in the case of aneurysms with complex geometries the operative planning is still complicated, so the development of the real three-dimensional physical model becomes advantageous. In this work, the entire process of manufacturing an aneurysm biomodel using polydimethylsiloxane (PDMS) is disassembled by rapid prototyping technology. The manufactured biomodels are able to perform different hemodynamic studies, validate theoretical data, numerical simulations and assist in the preoperative planning.